2012
DOI: 10.1248/bpb.35.362
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Percutaneous Absorption in Human Using Three-Dimensional Human Cultured Epidermis LabCyte EPI-MODEL

Abstract: The objective of this study is to establish a relationship of the skin penetration parameters between the three-dimensional cultured human epidermis LabCyte EPI-MODEL (LabCyte) and hairless mouse (HLM) skin penetration in vitro and to predict the skin penetration and plasma concentration profile in human. The skin penetration experiments through LabCyte and HLM skin were investigated using 19 drugs that have a different molecular weight and lipophilicity. The penetration flux for LabCyte reached 30 times large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…That is the reason for the observation of the relationship in DL −2 and KL between silicone membrane and human or animal skin in the present study. Previously, the permeabilities in human skin and hairless rat skin have been shown to correlate with those in alternative membranes, such as a three-dimensional cultured human skin model, [5][6][7] PAMPA, [8][9][10] and Strat-M . 11) On the other hand, silicone membranes have long been available as an alternative membrane in in vitro permeation studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is the reason for the observation of the relationship in DL −2 and KL between silicone membrane and human or animal skin in the present study. Previously, the permeabilities in human skin and hairless rat skin have been shown to correlate with those in alternative membranes, such as a three-dimensional cultured human skin model, [5][6][7] PAMPA, [8][9][10] and Strat-M . 11) On the other hand, silicone membranes have long been available as an alternative membrane in in vitro permeation studies.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro permeation studies of various model compounds have been conducted using a three-dimensional cultured human skin model, [5][6][7] a parallel artificial membrane permeability assay (PAMPA), [8][9][10] and Strat-M , 11) and these studies have shown the utility of skin surrogates. A study of silicone membrane permeability has been conducted previously, 12) and silicone has been used in various other studies to determine, for example, the effects of vehicles on membrane permeability, 13) prediction of skin concentrations of test compounds, 14) and skin permeation routes.…”
mentioning
confidence: 99%
“…While it is has been shown that the stratum corneum structure in the LabCyte EPI-MODEL24 delays the permeation of chemicals 21 , the barrier function of the LabCyte EPI-MODEL24 is weaker than that observed in humans and animals 22 . Surfactants, such as AS and MES, must easily permeate and disturb the protein and lipid domains in the epidermis.…”
Section: Effect Of Surfactants On Substances In the Epidermismentioning
confidence: 92%
“…Some reports were published using SKIN‐CAD ® for prediction of in vivo skin permeability . The predictions were based on the result of in vitro skin permeation experiments using animal skins or three‐dimensional human cultured epidermis.…”
Section: Methodsmentioning
confidence: 99%
“…Some reports were published using SKIN-CAD R for prediction of in vivo skin permeability. 7,14,[18][19][20] The predictions were based on the result of in vitro skin permeation experiments using animal skins or three-dimensional human cultured epidermis. This study is the first approach predicting human plasma concentration profiles using the result of in vitro human skin permeation experiments and SKIN-CAD R .…”
Section: Skin Pharmacokinetic Simulation Software Skin-cad Rmentioning
confidence: 99%